RESULTAN DARI POLINOMIAL DENGAN n - INDETERMINATE - Harjito, Harjito; Soelistyo, Robertus Heri; DR, Karuniawati (MATEMATIKA, 2007)
Let be polynomials where K is a field. To determine whether two polynomials have a common factor without doing any divisions in K[x] can be seen from its resultant, that is determinant from Sylvester matrix. Two polynomials will have a common factor if and only if its resultant is zero. If its resultant isn’t zero so two polynomials have not a common factor. Wants to be look for resultant where in where C is the set of all complex numbers. To make the easy resultant computations is used by maple 8.